Evaluation of Institutional Research Productivity - Pal, Jiban K.; Sarkar, Soumitra (DESIDOC Journal of Library & Information Technology, 2020)
The quantification of scholarly performance has become an obvious necessity in many academic pursuits. Evaluation of research output is therefore an integral element of R&D institutions worldwide. However the quality- weighted dimensions of quantity are gaining momentum. Consequently, a good number of evaluative studies on publication productivity have been made available in scientometric literature. This paper critically scrutinises the literature on research productivity concerning scientific institutions (include universities and departments) in an informational context. It provides a thorough review to map the quantum of knowledge relating to ‘institutional research productivity’ correlating the Indian vista. It is, however, indicative to find the gaps and shortcomings in this specialty of research; hence enunciate the issues both attended and unattended. The paper also offers a few recommendations to undertake evaluative studies with caution. Thus it shows a coherent picture of this emerging area in the sociology of science.